Effect of thermal fluctuations in topological p-wave superconductors - Bauer, Bela; Lutchyn, Roman; Hastings, Matthew; Troyer, Matthias (Physical Review B, 2013)
We study the effect of thermal fluctuations on the topological stability of chiral p-wave superconductors. We consider two models of superconductors: spinless and spinful with a focus on topological properties and Majorana zero-energy modes. We show that proliferation of vortex-antivortex pairs above the Kosterlitz-Thouless temperature TKT drives the transition from a thermal Quantum Hall insulator to a thermal metal/insulator, and dramatically modifies the ground-state degeneracy splitting. Therefore, in order to utilize 2D chiral p-wave superconductors for topological quantum computing, the temperature should be much smaller than TKT. Within the spinful chiral p-wave model, we also investigate the interplay between half-quantum vortices carrying Majorana zeroenergy modes and full-quantum vortices having trivial topological charge, and discuss topological properties of half-quantum vortices in the background of proliferating full-quantum vortices.